The Impact of Shopee's Free Shipping Feature on Consumer Loyalty - Uchi Ramadani; Ninis Desrianti; Faradilla Ismail; Erwina Erwina; Haeril Haeril (Sean Institute, 2026)
This study examined the effect of the free-shipping feature on the Shopee application toward consumer loyalty among residents of Kelurahan Battang Km 07, Palopo City. A quantitative approach was used, with a questionnaire distributed to 40 respondents selected through incidental sampling from a population of 150 active Shopee users aged 18–45 years. The data were analyzed descriptively using a Likert scale and inferentially through simple linear regression, preceded by validity, reliability, and classical assumption tests. The results showed that the free-shipping feature had a positive and significant effect on consumer loyalty, with a regression equation of Y = 0.489 + 0.939X, a t-value of 8.679 (sig. 0.000), and an R Square of 0.665, indicating that 66.5% of the variance in consumer loyalty was explained by the free-shipping feature. These findings confirm that free shipping functions not merely as a short-term promotion but as a long-term marketing strategy that strengthens Shopee's competitive advantage, contributing practical insight for e-commerce platforms in designing sustainable promotional strategies.